Emotion, Health, Personalization and User Empowerment: LIFeS Research Aligned with GranDIHC-BR 2025-2035 - Neris, Vânia P. A.; Souza, Paula M.; Borges, Alessandro C.; Ancioto, Alex Sandro R.; Ribeiro, Evandro Y. A.; Silva, Grasiane C.; Dominguete, Gustavo L.; Rodrigues, Stefane M.; Alves, Vanessa C. (Companion Proceedings of the Brazilian Symposium on Human Factors in Computational Systems (IHC); 2025: Companion Proceedings of the 24th Brazilian Symposium on Human Factors in Computational Systems, 2025)
Introduction: The Grand Challenges in Human-Computer Interaction (HCI) in Brazil (GranDIHC-BR 2025-2035) shed light on the future of HCI research in Brazil and worldwide. In this context, the Flexible and Sustainable Interaction Laboratory (LIFeS) has been working to advance the state of the art, particularly in topics related to personalization and user empowerment. Objective: This position paper presents a synthesis of the group's research, relating it to the challenges, and summarizes reflections for the future. Methodology: The text, constructed collaboratively, presents the group's own vision. Results: The group's research can be considered examples of actions, aligned with GranDIHC-BR 2025-2035, aiming to seek collaborations and support advancement in the field.